The perceptions of Moroccan trainee teachers regarding the gender approach and its implementation in the classroom - Abid, Mohammed; Bouali, Mostafa; El Andaloussi, Bouchra; Messaoud, Said (Frontiers in Education, 2025)
This study examines the perception of teachers in initial training teachers regarding the gender approach and its application in their pedagogical practices. The main research question and the secondary questions explore several aspects: teachers’ representations of the gender approach, their level of knowledge of this approach, their attitude toward gender equality, and the influence of gender and the subject taught on their teaching approaches. The study used a descriptive-analytical method with a sample of 196 trainee teachers (73% women, 27% men) from various disciplines and from the Regional Centers for Education and Training Professions of Rabat and Khénifra, Morocco, during the 2023/2024 training year. Data was collected using scale with six Likert levels, which evaluates teachers’ effectiveness in terms of gender knowledge, implementation of gender-sensitive pedagogical methods, and development of equality attitudes. The first axis focused on the knowledge and awareness of gender among trainee teachers and revealed that this element is above the “Somewhat Agree” level for the majority of participants. The same result, slightly lower, is noted for axes 2 and 3; which suggests that the trainee teachers in the sample are in the process of developing their representations and their own views on gender issues. Therefore, verifying the initial hypothesis regarding gender awareness and knowledge shows that the goal is not fully achieved. To strengthen the achievements of teachers, whether trainees or certified, continuous training remains the most effective means in this regard. Similarly, initial training should place more emphasis on the gender approach, especially in modules where this theme can be freely addressed, such as legislation and ethics, school life, and research methodology.